Cesium Lead Halide Perovskite Nanocrystals Assembled in Metal‐Organic Frameworks for Stable Blue Light Emitting Diodes. Issue 14 (15th March 2022) - Tsai, Hsinhan; Huang, Hsin‐Hsiang; Watt, John; Hou, Cheng‐Hung; Strzalka, Joseph; Shyue, Jing‐Jong; Wang, Leeyih; Nie, Wanyi
Abstract: All inorganic cesium lead trihalide nanocrystals are promising light emitters for bright light emitting diodes (LEDs). Here, CsPb(BrCl)1.5 nanocrystals in metal‐organic frameworks (MOF) thin films are demonstrated to achieve bright and stable blue LEDs. The lead metal nodes in the MOF thin film react with Cs‐halide salts, resulting in 10–20 nm nanocrystals. This is revealed by X‐ray scattering and transmission electron microscopy. Employing the CsPbX3 ‐MOF thin films as emission layers, bright deep blue and sky‐blue LEDs are demonstrated that emit at 452 and 476 nm respectively. The maximum external quantum efficiencies of these devices are 0.72% for deep blue LEDs and 5.6% for sky blue LEDs. More importantly, the device can maintain 50% of its original electroluminescence ( T 50 ) for 2.23 h when driving at 4.2 V. Detailed optical spectroscopy and time‐of‐flight secondary ion mass spectroscopy suggest that the ion migration can be suppressed that maintains the emission brightness and spectra. The study provides a new route for fabricating stable blue light emitting diodes with all‐inorganic perovskite nanocrystals. Abstract : A new strategy is demonstrated for integrating Cs‐based perovskites nanocrystal in metal‐organic framework (MOF) thin films with bright emissions from green to deep blue. The light emitting diodes made with MOF protect perovskite nanocrystal exhibit high performance electroluminescence with external quantum efficiencies of 5.6% and extended operation lifetime over 2 h.